Assessing the Awareness and Use of ICT Tools among University Students in Nigeria: Implications for Digital Literacy - Oyigan, Diseiye; Okiy, Rose Benin; Emojorho, Daniel (International Journal of Multidisciplinary Approach Research and Science, 2026)
The study examined assessing the awareness and use of ICT tools among university students in Nigeria: Implications for digital literacy. ICT tools in the case of higher education denote a vast array of technological tools utilized in communication, creation, dissemination, storage, and management of information. The research design used was a descriptive survey research. The study population consisted of undergraduate students in the Nigerian universities. Currently, according to the National Universities Commission (NUC) data, more than 2.3 million undergraduates study at 43 federal universities, 48 state universities, and 79 private universities of the country. A sample population of 585 respondents was picked out of an estimated population of 656 qualified students who had undergone or had access to institutional ICT facilities in the chosen universities, or participated in ICT-related courses. The findings indicate that ICT use in communication, internet use, and social networking were highly used by students and academic ICT use was less prevalent (data analysis, reference management, and e-library access).  The results have wide implications on the development of digital-literacy in universities in Nigeria.  The study concluded that ICT awareness among the Nigerian university students is high, but not evenly distributed among the institutions. Most students are conversant with the general ICT tools yet they have inadequate skills on academic-specific technologies that are vital in academics interaction. It was recommended that ICT cannot be isolated to be taught in computer science departments but it must be mainstreamed to all courses. The course evaluation may incorporate the Internet-based elements, online portfolios or e-projects submission to promote active ICT use.